Efficacy of herbicides applied to Digitaria horizontalis plants under different water conditions - Pereira,M.R.R. (2012)
This project aimed to relate the control efficiency of ACCase inhibiting herbicides applied post-emergence to Digitaria horizontalis plants under different soil water contents. The experiments were conducted in a greenhouse, with the application of three different herbicides (fluazifop-p-butyl, haloxyfop-methyl, and sethoxydim + mineral oil Assist). The experimental design used for each herbicide was completely randomized, with four replications, consisting of a 3 x 4 factorial, with the combination of water management strategies (-0.03, -0.07 and -1.5 MPa) and four doses of these products (100%, 50%, 25%, and 0% of the recommended dose). Herbicide application was made at two vegetative stages, 4-6 leaves and 2-3 tillers. The visual phytotoxicity evaluations were performed at 14 days after application and the plant dry weight at the end of the study was evaluated. The control efficiency was not affected by water management strategies when applied to the recommended dose of the herbicides in early stages of plant development (4-6 leaf stage). In late applications (2-3 tiller stage) the plants held under drought stress showed less phytotoxicity.